Use of cervicofacial flap for reconstruction of extensive facial damage following Mohs surgery: a case report - Maria Carolina Casa Souza; Fernando Eibs Cafrune (Sociedade Brasileira de Dermatologia (SBD), 2020)
Introduction: Facial skin cancer can be very challenging to surgical treatment. Reconstruction with cervicofacial flap is an adequate option when extensive damage is present. We describe a surgical procedure for complex lesions with high morbidity potential. Case study: 69-year-old woman with a large, recurring sclerodermiform basal cell carcinoma (BCC) in the left zygomatic area. Due to the lesion characteristics, we opt to perform Mohs surgery. A cervicofacial flap was used with good aesthetic results and no relapse. Discussion: The cervicofacial flap is ideal for extensively damaged areas and can be used as an alternative to skin graft.